A new species of fossil Procercopidae (Hemiptera, Cicadomorpha) from the Lower Cretaceous of Northeastern China. (January 2015) - Chen, Dong; Yao, Yunzhi; Ren, Dong
Abstract: New fossil genus with a new species, Stellularis longirostris Chen, Yao and Ren, gen. et sp. nov., from the family Procercopidae, are described. New specimens were collected from the Lower Cretaceous non-marine sedimentary strata from the Yixian Formations of northeast China. The exceptionally well-preserved materials reveal fine details of the body structure and morphology including rostrum, legs, abdomen, anteclypeus and ovipositor. The genera Luanpingia Hong, 1983 and Cathaycixius Ren, Lu, and Guo, 1995 are discussed.